Improvement of Airflow Limitation by Fluticasone Propionate/Salmeterol in Chronic Obstructive Pulmonary Disease: What is the Specific Marker? - Akamatsu, Keiichiro; Matsunaga, Kazuto; Sugiura, Hisatoshi; Koarai, Akira; Hirano, Tsunahiko; Minakata, Yoshiaki; Ichinose, Masakazu (Frontiers in Pharmacology, 2011)
Backgrounds: Inhaled corticosteroids (ICS)/inhaled long-acting beta2-agonists (LABA) combination drugs are widely used for the long-term management of COPD. However, COPD is a heterogeneous condition and treatment with ICS is associated with a higher risk of pneumonia. The identification of a specific marker for predicting the efficacy of ICS/LABA on pulmonary function would be useful in the treatment of COPD. Methods: Fourteen COPD patients receiving tiotropium therapy participated consecutively. The relationship between the baseline exhaled nitric oxide (FENO) levels as well as serum markers and changes in pulmonary function by fluticasone propionate (FP)/salmeterol (SAL) were analyzed. Results: FP/SAL therapy significantly improved forced vital capacity, forced expiratory volume in one second (FEV1), and the third phase slope of the single nitrogen washout curve (ΔN2) as well as the FENO level. The baseline FENO levels and positive specific IgE (atopy+) were significantly associated with airway obstructive changes assessed by FEV1 and ΔN2. A baseline FENO level > 35 ppb yielded 80.0 % sensitivity and 66.7 % specificity for identifying the subjects with significant improvement in FEV1 (greater than 200 mL). An atopy+ yielded 60.0% sensitivity and 88.9% specificity for an improvement in FEV1. When combined with FENO > 35 ppb and atopy+, it showed 40% sensitivity and 100.0% specificity for FEV1 improvement. Alternatively, COPD subjects with FENO ≤ 35 ppb and atopy- did not show significant improvement in FEV1. Conclusions: Combining FENO and specific IgE may be a useful marker for predicting the response to ICS/LABA on airflow limitation in COPD.